1983
DOI: 10.1021/bk-1983-0221.ch002
|View full text |Cite
|
Sign up to set email alerts
|

Elastomeric Polysiloxane Modifiers for Epoxy Networks

Abstract: Novel elastomeric polysiloxane modifiers for epoxy networks have been synthesized and characterized. In addition, curing studies of conventional epoxy resins incorporating these oligo mers have been conducted. Structures were prepared having either epoxide, primary amine and/or secondary amine endgroups. The polymerization step for the siloxanes consisted of a base cata lyzed equilibration of the appropriately functionalized disiloxane and octamethylcyclotetrasiloxane. In the case of hydroxy piperazine termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 10 publications
(12 reference statements)
0
20
0
1
Order By: Relevance
“…Further work may be related to the improvement of the thermodynamic and kinetic basis by removing some of the hypotheses carried out in the analysis, or to the extension to formulations using different rubbers than butadiene-acrylonitrile copolymers, like polysiloxanes or polyacrylates, [24][25][26][27] or to the use of engineering thermoplastics like PES or PEI in epoxy formulations.2a32 In this last case, new situations, like the vitrification curve of the epoxy copolymer-engineering thermoplastic, have to be considered in the analysis, because phase separation may be constrained by vitrification, depending on the location of the predicted composition for the dispersed phase and the Tg vs. composition curve. Of great interest will be also to follow the evolution of morphology at the early stages of phase separation.…”
Section: Discussionmentioning
confidence: 99%
“…Further work may be related to the improvement of the thermodynamic and kinetic basis by removing some of the hypotheses carried out in the analysis, or to the extension to formulations using different rubbers than butadiene-acrylonitrile copolymers, like polysiloxanes or polyacrylates, [24][25][26][27] or to the use of engineering thermoplastics like PES or PEI in epoxy formulations.2a32 In this last case, new situations, like the vitrification curve of the epoxy copolymer-engineering thermoplastic, have to be considered in the analysis, because phase separation may be constrained by vitrification, depending on the location of the predicted composition for the dispersed phase and the Tg vs. composition curve. Of great interest will be also to follow the evolution of morphology at the early stages of phase separation.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 We have previously reported the synthesis of 1,9-bis[glycidyloxypropyl]decamethylpentasiloxane (I), 1,9-bis[glycidyloxypropyl]-3,5,7-tris(3Ј,3Ј,3Ј-trifluoropropyl)heptamethylpentasiloxane (II), and 1,9-bis-[glycidyloxypropyl]-3,5,7-tris(1ЈH,1ЈH,2ЈH,2ЈH-perfluorooctyl)heptamethylpentasiloxane (III). 35 In contrast to other studies with siloxane or fluorinated modified epoxies, 10,[32][33][34] these have well-defined microstructures. This may be useful in establishing structure-property relationships.…”
Section: Introductionmentioning
confidence: 96%
“…4 -16 These undergo phase separation during curing to form randomly dispersed particles within the epoxy matrix. Rubber or elastomeric modifiers that have been studied include carboxy-and amine-terminated butadiene-acrylonitrile copolymers, 4 polyacrylate elastomers, 5 poly(propylene oxide), 6 polysiloxanes, [7][8][9][10] and fluoroelastomers. 11 Unfortunately, small amounts of rubbery modifiers dissolved in the matrix cause a decrease in the T g and modulus values of epoxy resins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also widely known owing to its extremely low glass transition temperature, flexibility and hydrophobic surface properties. [5][6][7][8] These properties of PDMS make it suitable for use in different industries. [9][10][11][12][13] Several studies have been reported on the phase behavior of PE/PDMS composites.…”
Section: Introductionmentioning
confidence: 99%